Antioxidants in the extract of balinese salak rind (Salacca amboinensis (Becc) Mogea) as an alternative substance to decrease blood sugar levels among Mus musculus L. with hyperglycemia - Ida Ayu Manik Damayanti; Ni Wayan Sukma Antari; Sri Dewi Megayanti; Kadek Buja Harditya; I Made Bayu Jaya Kusuma; Ni Wayan Kesari Dharmapatni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to determine the antioxidant potential of Balinese salak rind extract (Salacca amboinensis (Becc) Mogea) (BSRE) as an antihyperglycemic agent in male white mice with hyperglycemia. The research was conducted in three stages extraction of Balinese salak rind using 96% ethanol, phytochemical screening, and antihyperglycemic activity testing. Mice were hyperglycemia induced by alloxan. Mice were divided into five groups consisting of negative control (Aquadest), positive control (Glibenclamide 13 mg/Kg BW), dose 1 (200 mg BSRE/kg BW), dose 2 (400 mg BSRE/kg BW), dose 3 (600 mg BSRE/kg BW). Phytochemical screening showed that the BSRE was positive for containing alkaloids, flavonoids, tannins, saponins, and steroids. The analysis results on the BSRE showed an IC50 value of 81,76 ppm, including strong antioxidant activity. The activity of blood glucose levels showed that BSRE could decrease blood glucose levels of Mus musculus L. with hyperglycemia.